2009
DOI: 10.1063/1.3272678
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic anisotropy of thermal conductance in graphene nanoribbons

Abstract: Thermal conductance of graphene nanoribbons (GNRs) with the width varying from 0.5 to 35 nm is systematically investigated using nonequilibrium Green's function method. Anisotropic thermal conductance is observed with the room temperature thermal conductance of zigzag GNRs up to ~ 30% larger than that of armchair GNRs. At room temperature, the anisotropy is found to disappear until the width is larger than 100 nm. This intrinsic anisotropy originate from different boundary condition at ribbon edges, and can be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
164
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 22 publications
11
164
0
Order By: Relevance
“…Due to different boundary condition, intrinsic anisotropy thermal conductivity of GNR is reported. 114 As shown in Fig. 7(a), the room temperature thermal conductance of zigzag GNR is about thirty percent larger than that of armchiar GNR.…”
Section: B 2d Nanostructuresmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to different boundary condition, intrinsic anisotropy thermal conductivity of GNR is reported. 114 As shown in Fig. 7(a), the room temperature thermal conductance of zigzag GNR is about thirty percent larger than that of armchiar GNR.…”
Section: B 2d Nanostructuresmentioning
confidence: 94%
“…There are rich physical phenomena about thermal property of GNRs. The effects of size, [95][96][97][98] defects, 99, 100 doping, 101,102 shape, 103,104 stress/strain,, [105][106][107][108] substrates, 109 inter-layer interactions, [110][111][112] nanoscale junctions, 113 chirality, 114 topological structure, 115 edge effect, [116][117][118][119] foldings (gradfolds), 23,120 etc. on thermal conductivity of nanoribbons [121][122][123][124][125][126][127][128] have been widely studied.…”
Section: B 2d Nanostructuresmentioning
confidence: 99%
“…The measured value of thermal conductivity of graphene reaches as high as several thousand of watt per meter Kelvin, [7][8][9][10] among the highest values of known materials. Previous studies [11][12][13] show that the thermal transport in GNRs depends on the edge chirality of GNRs. In realistic graphene samples, the edges are often passivated [14][15][16] and the isotope composition can be controlled.…”
mentioning
confidence: 99%
“…Within each slice ͓such as the dashed box in the inset of Fig. 3͑b͔͒, the number ͑L͒ of vertical 13 C atomic chains with zigzag shape ͓e.g., L = 4 for the inset of Fig. 3͑b͔͒ can vary from 0 to 7 ͑see details in Ref.…”
mentioning
confidence: 99%
“…Several studies have shown that armchair edge GNRs (AGNRs -the ones considerd in the main text) and zig-zag-GNRs (ZGNRs) differ in thermal conductivity [41,[59][60][61][62]. Thus, we find it instructive to present the corresponding simulation results as in Fig.…”
Section: Appendix: Simulation Data For the Zigzag-edge Gnrs (Zgnrs)mentioning
confidence: 99%